2022
DOI: 10.1186/s12888-022-03947-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations between self-reported psychological symptom severity and gut microbiota: further support for the microgenderome

Abstract: Background Research into the brain-gut-microbiota axis (BGMA) continues to reveal associations between gut microbiota (GM) and psychological symptom expression, inspiring new ways of conceptualising psychological disorders. However, before GM modulation can be touted as a possible auxiliary treatment option, more research is needed as inconsistencies in previous findings regarding these associations are prevalent. Additionally, the concept of the microgenderome, which proposes that GM may inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 132 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…Women tend to exhibit higher levels compared to men [ 39 , 40 , 41 , 42 ]. Bifidobacterium and Clostridium , which are closely associated with these psychological and cognitive disorders, may be potential therapeutic targets, especially in the female population [ 43 ]. In addition, the genus Clostridium is associated with various metabolic pathways, including arginine metabolism, proline metabolism, and fatty acid biosynthesis, and is linked to a broad network of functional connections that mediate the relationship between Clostridium -associated metabolic pathways and cognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women tend to exhibit higher levels compared to men [ 39 , 40 , 41 , 42 ]. Bifidobacterium and Clostridium , which are closely associated with these psychological and cognitive disorders, may be potential therapeutic targets, especially in the female population [ 43 ]. In addition, the genus Clostridium is associated with various metabolic pathways, including arginine metabolism, proline metabolism, and fatty acid biosynthesis, and is linked to a broad network of functional connections that mediate the relationship between Clostridium -associated metabolic pathways and cognition.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that the abundance of g_ Bifidobacterium , f_ Lactobacillaceae , and g_ Lactobacillus in the DK group was significantly higher than that in the CK group. As previously mentioned, g_ Bifidobacterium is closely related to depression, neurocognition, stress, and anxiety, and may serve as a potential target for the treatment of psychological and cognitive disorders [ 43 ]. g_ Lactobacillaceae (at the family or genus level) is also closely related to emotions and cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it could aid the development of personalized nutritional therapies by identifying next generation probiotics species to be tested in anxiety treatment – analogously to what is currently being done for major depressive disorder (Zorzan and Barberis, personal communication) – and by taking into account sex-based variations. Indeed, sex-specific associations also occur between gut microbiome and anxiety severity at the species level as pinpointed in a study by Ganci et al ( 16 ): in males, Alistipes shahii was negatively associated with anxiety; in females (males), Lactobacillus paracasei ( Lactobacillus plantarum ) and Streptococcus dysgalactiae ( Streptococcus gallolyticus ) were positively associated with anxiety. Jiang et al ( 17 ) also observed that probiotics supplementation differentially alleviates anxiety-like behaviors in male and female animal models.…”
Section: Introductionmentioning
confidence: 94%
“…The authors also showed lower relative abundance of Prevotella (Bacteroidetes phylum) in anxious female participants. Likewise, Ganci et al ( 16 ) identified sex-specific relationships in females, noting both positive and negative associations between anxiety symptoms and specific Firmicutes species, including negative associations with Clostridium innocuum, Enterococcus durans, Leuconostoc lactis, Ruminococcus gnavus and positive associations with Lactobacillus paracasei , and Streptococcus dysgalactiae . In a study investigating positive and negative affect, Lee et al ( 35 ) found that Collinsella (Actinobacteria phylum) was inversely associated with positive affect, whereas a new genus from the Lachnospiraceae family (PAC001043) showed a positive association with positive affect and a negative association with negative affect.…”
Section: Diet Gut Microbiome and Anxiety: Integrating Available Evide...mentioning
confidence: 99%
See 1 more Smart Citation